Alterations in macrophage polarization in the craniofacial and extracranial skeleton after zoledronate application and surgical interventions – an in vivo experiment - Struckmeier, Ann-Kristin; Wehrhan, Falk; Preidl, Raimund; Mike, Melanie; Mönch, Tina; Eilers, Lea; Ries, Jutta; Trumet, Leah; Lutz, Rainer; Geppert, Carol; Kesting, Marco; Weber, Manuel (Frontiers in Immunology, 2023)
Background: Medication-related osteonecrosis occurs exclusively in the jaw bones. However, the exact pathogenesis of medication-related osteonecrosis of the jaw (MRONJ) and the unique predisposition of the jaw bones have not been elucidated, making its treatment a challenge. Recent evidence indicates that macrophages might play a pivotal role in MRONJ pathogenesis. The aim of the present study was to compare the macrophage populations between the craniofacial and extracranial skeleton and to investigate the changes induced by zoledronate (Zol) application and surgical interventions. Methods: An in vivo experiment was performed. 120 wistar rats were randomized to 4 groups (G1, G2, G3, G4). G1 served as an untreated control group. G2 and G4 received Zol injections for 8 weeks. Afterwards, the right lower molar of the animals from G3 and G4 was extracted and the right tibia osteotomized followed by osteosynthesis. Tissue samples were taken from the extraction socket and the tibia fracture at fixed time points. Immunohistochemistry was conducted to determine the labeling indexes of CD68+ and CD163+ macrophages. Results: Comparing the mandible and the tibia, we observed a significantly higher number of macrophages and a heightened pro-inflammatory microenvironment in the mandible compared to the tibia. Tooth extraction caused an increase of the overall number of macrophages and a shift toward a more pro-inflammatory microenvironment in the mandible. Zol application amplified this effect. Conclusions: Our results indicate fundamental immunological differences between the jaw bone and the tibia, which might be a reason for the unique predisposition for MRONJ in the jaw bones. The more pro-inflammatory microenvironment after Zol application and tooth extraction in the jaw bone might contribute to the pathogenesis of MRONJ. Targeting macrophages might represent an attractive strategy to prevent MRONJ and improve therapy. In addition, our results support the hypothesis of an anti-tumoral and anti-metastatic effect induced by BPs. However, further studies are needed to delineate the mechanisms and specify the contributions of the various macrophage phenotypes.